Research progress on the mechanism of cerebral blood flow regulation in hypoxia environment at plateau. Issue 3 (1st March 2022) - Hao, Gui-Sheng; Fan, Qing-Li; Hu, Quan-Zhong; Hou, Qian
ABSTRACT: The plateau is a special environment with low air pressure and low oxygen content. The average altitude of Qinghai-Tibet is 3, 500 m, and the atmospheric oxygen partial pressure in most areas is lower than 60% of that at sea level. In order to adapt to the plateau low-oxygen environment, the human body has developed corresponding physiological structure and functions adjust. In the present review, the regulation mechanism of cerebral blood flow (CBF) under high-altitude environments was elaborated in eight aspects: the arterial blood gas, endogenous substances in the nerve and blood, the cerebral neovascularization, the hematocrit, cerebral auto-regulation mechanism, cerebrovascular reactivity, pulmonary vasoconstriction, and sympathetic automatic regulation, aiming to further explore the characteristics of changes in brain tissue and cerebral blood flow in a hypoxic environment.